1984
DOI: 10.1139/o84-108
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein C-II deficiency associated with nonfunctional mutant forms of apolipoprotein C-II

Abstract: Two previously unidentified apolipoproteins (apo) designated apo C-II-X and C-II-Y have been found in plasma of homozygotes and obligate heterozygotes of a family with apo C-II deficiency. Because the plasma of homozygotes do not activate lipoprotein lipase, apo C-II-X and C-II-Y are apparently nonfunctional. These apolipoproteins have isoelectric focusing points of 5.15 and 5.54, respectively, compared with 4.88 and 4.74 for the known isomorphs, C-II-1 and C-II-2, respectively. They have approximately similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…We previously reported that the 14 homozygotes and 23 obligate heterozygotes from the apoCII-deficient family described by this laboratory are characterized by the presence of a mutant, nonfunctional apoCII, apoCIITOrmftO (apoCIIT) (11).…”
mentioning
confidence: 99%
“…We previously reported that the 14 homozygotes and 23 obligate heterozygotes from the apoCII-deficient family described by this laboratory are characterized by the presence of a mutant, nonfunctional apoCII, apoCIITOrmftO (apoCIIT) (11).…”
mentioning
confidence: 99%
“…The lyophilized protein was delipidated with ethanol/diethylether (11). The analysis of this acetone-soluble product by analytical polyacrylamide isoelectric focusing using a pH 4-6.5 gradient showed it to contain apoC-IIT and the isomorphs of apolipoprotein C-IIIi.e., C-III-0, C-III-1, and C-III-2 (8).…”
Section: Methodsmentioning
confidence: 98%
“…The viscous oil-like residue present was extracted with 5 ml of chloroform/methanol (2:1) at room temperature to produce a white powder. ApoC-IIT was identified by analytical isoelectric focusing and shown to be homogeneous (8). Normal apoC-II was isolated from a control subject following the identical protocol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations